Estrategias para motivar a la lectura comprensiva, a los niños y niñas de 7MO grado paralelo b de la escuela de educación básica Dra. Matilde hidalgo de Procel N°1 de la ciudad de Loja, barrio san pedro en el período lectivo 2013-2014 - Cordova Pasaca, Andres Estuardo (2016)
This research work called STRATEGIES TO MOTIVATE COMPREHENSIVE READING, THE CHILDREN OF PARALLEL B 7TH GRADE SCHOOL OF BASIC EDUCATION DRA. MATILDE HIDALGO NO. 1 LOJA CITY, SAN PEDRO NEIGHBORHOOD IN PERIOD LECTIVO 2013-2014, aimed to understand the theoretical foundation of motivational strategies in reading comprehension, diagnose difficulties encountered by not use appropriate motivational strategies in reading comprehension during the teaching-learning process, creating alternative guidance on methodological strategies for motivating comprehensive reading to help improve the teaching - learning in children of Seventh Year Basic General Education parallel B, implementing strategies for motivation to reading comprehension in the educational process and improve learning, vocabulary and cognitive ability in children, to evaluate the effectiveness of the implementation of strategies for motivating comprehensive reading promote quality and warmth of the teaching-learning process and identify strategies motivational reading comprehension, for children in seventh B to encourage and promote the quality and warmth of teaching learning process. To carry out this investigation the cross and pre-experimental design was used, and comprehensive, analytical, synthetic, model or proactive methods, workshop and comprehensive evaluation method used; the following techniques as well as direct observation and survey, which were guided observation and questionnaire. In the research work the research population was thirty-one human talents; 1 teacher and thirty students, the same the following results were obtained most students report that their teacher does not use strategies to motivate reading comprehension as these are very necessary for the development of reading skills; It concludes that strategies to encourage reading comprehension are an essential part in education; achieving an optimal student learning and therefore in their comprehensive training.